Society of others : kinship and mourning in a West Papuan place - Stasch, Rupert (Berkeley : University of California Press, 2009)
This important study upsets the popular assumption that human relations in small-scale societies are based on shared experience. In a theoretically innovative account of the lives of the Korowai of West Papua, Indonesia, Rupert Stasch shows that in this society, people organize their connections to each another around otherness. Analyzing the Korowai people's famous "tree house" dwellings, their patterns of living far apart, and their practices of kinship, marriage, and childbearing and rearing, Stasch argues that the Korowai actively make relations not out of what they have in common, but out.
Introduction: otherness as a relation -- A dispersed society: place ownership and the crossing of spatial margins -- Pairing and avoidance: an otherness-focused approach to social ties -- Strange kin: maternal uncles and the spectrum of relatives -- Children and the contingency of attachment -- Marriage as disruption and creation of belonging -- Dialectics of contact and separation in mourning -- Conclusion.
Includes bibliographical references (p. 291-301) and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
English.
JSTOR
Keywords: Ethnology -- Indonesia -- Papua; Kinship -- Indonesia -- Papua; Mourning customs -- Indonesia -- Papua; Ethnopsychology -- Indonesia -- Papua; Papua (Indonesia) -- Social life and customs; Ethnologie -- Indonésie -- Papouasie occidentale; Parenté -- Indonésie -- Papouasie occidentale; Deuil -- Coutumes -- Indonésie -- Papouasie occidentale; Ethnopsychologie -- Indonésie -- Papouasie occidentale; Papouasie occidentale (Indonésie) -- Mœurs et coutumes; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Ethnology; Ethnopsychology; Kinship; Manners and customs; Mourning customs; Indonesia -- Papua; Korowai (volk); Sociale relaties; Sociale structuur; Papua (Indonesië)